Linking chemistry and biology: protein sequences - Laos, Roberto (2016)
In the last twenty years, the number of complete genomes that have been sequenced and deposited in data banks has grown dramatically. This abundance in sequence information has supported the creation of the discipline known as  paleogenetics. In this article, without going into complex algorithms, we present some key concepts for understanding how proteins have evolved in time. We then illustrate how paleogenetic analysis can be used in biotechnology. These examples highlight the connection between chemistry and biology, two disciplines that twenty years ago seemed to be more different than what they seem to be today.